Numerical simulation of mechanical properties of short basalt fiber bundles reinforced concrete (SBFBRC). Issue 1 (1st January 2022) - Zhang, P; Lv, XL; Liu, Y; Shao, JG; Jin, YG; Li, CC; Huang, YJ
Abstract: The performance of short basalt fiber bundles reinforced concrete (SBFBRC) is studied in depth through numerical simulation. Based on the data of the flexural test of basalt fiber-reinforced concrete with 0% and 0.2% content, the basalt fiber-reinforced concrete is established by ABAQUS. The validity of the model is verified by the existing test data. The influence of basalt fiber bundle content, length, and diameter on the compressive strength of concrete is studied. The results show that the load-displacement curve obtained by the simulation in this paper is approximately the same as the curve obtained by the experiment, and the simulated peak load and peak deflection are similar to the average value of the test group, which reflects the accuracy of the model. Parameter analysis shows that with the increase of fiber bundle content, the strength and toughness of concrete gradually increase; the increase of basalt fiber bundle length has no obvious effect on improving the compressive strength of concrete; when the fiber bundle content is constant, it is increased appropriately. The aspect ratio of the fiber bundle is beneficial to the improvement of compressive strength and toughness.